Molecular variants and mutations in medulloblastoma - Schroeder K; Gururangan S (Dove Medical Press, 2014)
Kristin Schroeder, Sri GururanganPediatric Clinical Services, Preston Robert Tisch Brain Tumor Center at Duke, Duke University Medical Center, Durham, NC, USAAbstract: Medulloblastoma is the commonest malignant brain tumor in children. Treatment with surgery, irradiation, and chemotherapy has improved outcomes in recent years, but patients are frequently left with devastating neurocognitive and other sequelae following such therapy. While the prognosis has traditionally been based on conventional histopathology and clinical staging (based on age, extent of resection, and presence or absence of metastasis), it has become apparent in recent years that the inherent biology of the tumor plays a significant part in predicting survival and sometimes supersedes clinical or pathologic risk factors. The advent of deep sequencing gene technology has provided invaluable clues to the molecular makeup of this tumor and allowed neuro-oncologists to understand that medulloblastoma is an amalgamation of several distinct disease entities with unique clinical associations and behavior. This review is a concise summary of the pathology, genetic syndromes, recent advances in molecular subgrouping, and the associated gene mutations and copy number variations in medulloblastoma. The association of molecular alterations with patient prognosis is also discussed, but it should be remembered that further validation is required in prospective clinical trials utilizing uniform treatment approaches.Keywords: medulloblastoma, children, adults, molecular subgroups, mutations